2014
DOI: 10.1097/mnm.0000000000000043
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the 14C-urea breath test using indigenously produced 14C-urea capsules and a modified technique for trapping exhaled breath

Abstract: The carbon urea breath test ((14)C-UBT) is a noninvasive technique used to detect Helicobacter pylori infection in patients presenting with dyspeptic symptoms. The present study was undertaken to determine the efficacy of indigenously produced (14)C-UBT capsules by the Board of Radiation and Isotope Technology, India. Thirty consecutive patients with dyspeptic symptoms were included in the study. After ingestion of capsules, breath samples were collected in a CO2-trapping solution to which a scintillation cock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Patients enrolled in this study were surveyed and categorized as H. pylori positive (Hp+) or negative (Hp-) using urea breath test (UBT) and Hp stool antigen (HpSA) test for being noninvasive effective diagnostic tests. In line with the applied methodology, the results obtained by Tiwari et al [25] indicated that UBT may be employed after completion of eradication therapy to assure infection eradication and Ferwana et al [26] , (2015) out of literature meta-analysis concluded that UBT has high diagnostic accuracy for detecting Hp infection. Concerning HpSA test, Douraghi et al [27] reported that HpSA test is sensitive, non-invasive, valid screening modality for Hp as it detects the specific antigens shed during active infections, has less crossreactivity than serological antibodies detection tests.…”
Section: Discussionmentioning
confidence: 96%
“…Patients enrolled in this study were surveyed and categorized as H. pylori positive (Hp+) or negative (Hp-) using urea breath test (UBT) and Hp stool antigen (HpSA) test for being noninvasive effective diagnostic tests. In line with the applied methodology, the results obtained by Tiwari et al [25] indicated that UBT may be employed after completion of eradication therapy to assure infection eradication and Ferwana et al [26] , (2015) out of literature meta-analysis concluded that UBT has high diagnostic accuracy for detecting Hp infection. Concerning HpSA test, Douraghi et al [27] reported that HpSA test is sensitive, non-invasive, valid screening modality for Hp as it detects the specific antigens shed during active infections, has less crossreactivity than serological antibodies detection tests.…”
Section: Discussionmentioning
confidence: 96%